How motivation, time devoted to speaking practice, and teaching speaking methodology interfere in the oral performance in intermediate english students at the Foreign Language Department of the University of El Salvador in the Term I-2011 - Aguilar Mejía, Sandra Beatriz; Osorio Driotez, Elena Roxana; León Rivera, Ronald Omar; Guzmán Martínez, César Augusto; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2012)
Learning English has become a mandatory skill that many people should have. There are many reasons why people decide to study English as a second language, for example: to improve their financial situation, travel around the world, work abroad, communicatewith people from different countries, etc. It is very common to see people from different ages enrolling in academies and universities which offer an enticing academic program designed to fulfill the students’ necessities. Day by day, our society is moving into a globalized stage that is opening doors and offering opportunities to people who master a second language. Mastering a second language involves a process that requires dedication, practice, and motivation; this process plays an important role that helps us to be in touch with new cultures, technologies, societies, etc. Mastering the knowledge of English is classifiedby the level of the students; this mastering has three basic levels: beginner, intermediate, and advanced. Generally speaking beginners are those who do not know much English and advanced are those students whose level of English is competent. Between these two levels, intermediate implies that the speaker is ready to initiate, sustain, and close a conversation with a variety but limited vocabulary.
Anexos
Tesis -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2011
Audiencia general.
La tesis también está en formato digital.
Keywords: Inglés -- Enseñanza; Inglés -- Pronunciación; Comunicación oral